2015
DOI: 10.1186/s12968-015-0201-6
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular magnetic resonance techniques and findings in children with myocarditis: a multicenter retrospective study

Abstract: BackgroundCardiovascular magnetic resonance (CMR) is increasingly used to diagnose myocarditis in adults but its use in children is not well-established. We sought to describe the presentation, CMR protocol and findings, and outcomes in a multicenter cohort of children with myocarditis.MethodsThirteen hospitals retrospectively identified patients meeting the following inclusion criteria: 1) diagnosis of myocarditis by the managing physicians, 2) age <21 years, 3) CMR examination within 30 days of presentation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
59
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(70 citation statements)
references
References 27 publications
9
59
0
2
Order By: Relevance
“…In fact, the occurrence of JET is a good predictor for spontaneous recovery of AV conduction following the onset of postoperative CHB 10 . Unique to our case in support of this theory was evidence of both early and delayed gadolinium enhancement on cardiac MRI, 11 seen scattered throughout the ventricular septum, including the basal septum. With resolution of the JET and normalization of left ventricular function, antiarrhythmic medications were successfully discontinued.…”
Section: Discussionsupporting
confidence: 79%
“…In fact, the occurrence of JET is a good predictor for spontaneous recovery of AV conduction following the onset of postoperative CHB 10 . Unique to our case in support of this theory was evidence of both early and delayed gadolinium enhancement on cardiac MRI, 11 seen scattered throughout the ventricular septum, including the basal septum. With resolution of the JET and normalization of left ventricular function, antiarrhythmic medications were successfully discontinued.…”
Section: Discussionsupporting
confidence: 79%
“…High specificity of LGE for the detection of myocardial injury in myocarditis had been demonstrated in several studies (Cooper et al, 2007; Abdel-Aty et al, 2005; Mahrholdt et al, 2004). In our study, patchy mid-wall or subepicardial LGE in the LV walls were found in seven FM children (87.5%), which were similar to those in AM children (Banka et al, 2015; Sachdeva et al, 2015). Similar mid-wall LGE were also found in a 33-year-old female FM patient (Ryu et al, 2013).…”
Section: Discussionsupporting
confidence: 78%
“…Mechanically, myocardial inflammation can cause cardiac dysfunction and reduced ejection fraction (Lurz et al, 2012; Banka et al, 2015). Myocardial inflammation can also alter electrical impulse propagation by modulating gap junctional coupling (GJC) (Zhu et al, 2000; Xu H. F. et al, 2012), ionic currents (Tang et al, 2007; De Jesus et al, 2015), and tissue hydration state (Logstrup et al, 2015).…”
Section: Introductionmentioning
confidence: 99%